Mytella strigata and Mytella guyanensis as an object of study: scientific and popular nomenclature review, morphological aspects and occurrence in Babitonga Bay-SC/ Mytella strigata e Mytella guyanensis como objeto de estudo: revisão da nomenclatura científica e popular, aspectos morfológicos e ocorrência na Baia da Babitonga-SC - Beltrão, Mayara Carneiro; Baratieri, Letícia Zanatta; Diehl, Fernando Luiz (Brazilian Journal of Development, 2022)
Bivalve molluscs are an object of great economic interest, in the genus Mytella, it is possible to highlight the species Mytella strigata and Mytella guyanensis. The aim of this study was to carry out a review about the popular and scientific nomenclature of these species, evaluate the main characteristics used to differentiate them, as well as to carry out a quali-quantitative analysis of the mussels from the bay of Babitonga-SC. During the popular nomenclature review it turned out that the mussels M. guyanensis and M. strigata have gone through numerous revisions and nomenclature changes, as well as have several synonymous species. According to the studies reviewed to the popular nomenclature subject, 75% of the publications related to M. guyanensis and M. strigata were made in the Northeast, regarding the popular names “bacucu” and “sururu”, the second term was the most widespread. The analysis of the mussel stocks of Babitonga Bay demonstrated the predominance of M. guyanensis (96%). No significant difference was observed for the sample survey and collection station factors. However, the variations in abundance and diversity were significant for the stratum factor, where the highest values were recorded in the lower mesolittoral, suggesting a tendency for these organisms to be distributed in environments with less air exposure at low tide.